The ocean basins their structure and evolution / prepared by John Wright and David A. Rothery for the Course Team. - Wright, John (Butterworth-Heinemann ; Open University, 1998)
This is an invaluable textbook, prepared by the Open University team and designed so that it can be read on its own or as part of the OU course. This second edition has been fully revised and updated including new colour illustrations increasing the striking spread of full colour diagrams throughout the book. The clarity of the text has been improved, providing comprehensive coverage of the evolution of ocean basins and their structure in a clear, concise manner aimed specifically at the student market. In this second edition the technological advances in fields as diverse as:. - deep-towed in.
"Designed so that it can be read on its own or studied as part of the Open University third-level course, S330 Oceanography"--Page 4 of cover.
On p. facing title page: "Oceanography Course Team."
1st edition, 1989: prepared by an Open University course team [authors, Joan Brown and others]
Keywords: Submarine geology.; Paleoceanography.